Cannabis legalization and traffic injuries: exploring the role of supply mechanisms. (7th March 2022) - Kilmer, Beau; Rivera‐Aguirre, Ariadne; Queirolo, Rosario; Ramirez, Jessica; Cerdá, Magdalena
Abstract: Background and aim: In Uruguay, residents age 18 and older seeking legal cannabis must register with the government and choose one of three supply mechanisms: self‐cultivation, non‐profit cannabis clubs or pharmacies. This is the first paper to measure the association between type of legal cannabis supply mechanism and traffic crashes involving injuries. Design: Ecological study using ordinary least squares regression to examine how department‐level variation in registrations (overall and by type) is associated with traffic crashes involving injuries. Setting: Uruguay. Cases: 532 department‐quarters. Measurements: Quarterly cannabis registration counts at the department level and incident‐level traffic crash data were obtained from government agencies. The analyses controlled for department‐level economic and demographic characteristics and, as a robustness check, we included traffic violations involving alcohol for departments reporting this information. Department‐level data on crashes, registrations and alcohol violations were denominated by the number of residents ages 18 and older. Findings: From 2013 to 2019, the average number of registrations at the department‐quarter level per 10 000 residents age 18 and older for self‐cultivation, club membership and pharmacy purchasing were 17.7 (SD = 16.8), 3.6 (SD = 8.6), and 25.1 (SD = 50.4), respectively. In our multivariate regression analyses, we did not find a statistically significant association between the total number of registrations and traffic crashes with injuries (β = −0.007; P = 0.398; 95% CI = −0.023, 0.01). Analyses focused on the specific supply mechanisms found a consistent, positive and statistically significant association between the number of individuals registered as self‐cultivators and the number of traffic crashes with injuries (β = 0.194; P = 0.008; 95% CI = 0.058, 0.329). Associations for other supply mechanisms were inconsistent across the various model specifications. Conclusions: In Uruguay, the number of people allowed to self‐cultivate cannabis is positively associated with traffic crashes involving injuries. Individual‐level analyses are needed to assess better the factors underlying this association.